Influence of an Infectious Diseases Specialist on ICU Multidisciplinary Rounds - David N. Gilbert (Critical Care Research and Practice)
Objective. To ascertain the influence of a physician infectious diseases specialist (IDS) on antibiotic use in a medical/surgical intensive care unit. Method. Over a 5-month period, the antibiotic regimens ordered by the ICU multidisciplinary team were studied. The days of antibiotic therapy (DOT) when management decisions included an IDS were compared to DOT in the absence of an IDS. The associated treatment expense was calculated. Results. Prior to multidisciplinary rounds (MDRs), 79-80% of the patients were receiving one or more antibiotic. IDS participation occurred in 61 multidisciplinary rounding sessions. There were 384 patients who before MDRs had orders for 669 days of antimicrobial therapy (DOT). After MDRs, the antimicrobial DOT were reduced to 511 with a concomitant cost saving of $3772. There were 51 MDR sessions that occurred in the absence of the IDS. There were 352 patients who before MDRs had orders for 593 DOT. After MDRs, the DOT were reduced to 572 with a cost savings of $727. The results were normalized by number of patients evaluated with statistically greater reductions when MDRs included the IDS. In addition, the number of rounding sessions with a reduction in DOT was greater with the participation of the IDS. Conclusion. The addition of an IDS to multidisciplinary ICU patient rounds resulted in a reduction in antibiotic DOT and attendant drug expense.